100 kHz MAS Proton-Detected NMR Spectroscopy of Hepatitis B Virus Capsids - Lecoq, Lauriane; Schledorn, Maarten; Wang, Shishan; Smith-Penzel, Susanne; Malär, Alexander A.; Callon, Morgane; Nassal, Michael; Meier, Beat H.; Böckmann, Anja (Frontiers in Molecular Biosciences, 2019)
We sequentially assigned the fully-protonated capsids made from core proteins of the Hepatitis B virus using proton detection at 100 kHz magic-angle spinning (MAS) in 0.7 mm rotors and compare sensitivity and assignment completeness to previously obtained assignments using carbon-detection techniques in 3.2 mm rotors and 17.5 kHz MAS. We show that proton detection shows a global gain of a factor ~50 in mass sensitivity, but that signal-to-noise ratios and completeness of the assignment was somewhat higher for carbon-detected experiments for comparable experimental times. We also show that deuteration and HN back protonation improves the proton linewidth at 100 kHz MAS by a factor of 1.5, from an average of 170 to 110 Hz, and by a factor of 1.3 compared to deuterated capsids at 60 kHz MAS in a 1.3 mm rotor. Yet, several HN protons cannot be back-exchanged due to solvent inaccessibility, which results in a total of 15 % of the amides missing in the spectra.